The Role of the State in The Economy: Exploring Fiscal and Monetary Policies in Government (Theoretical Review in Islamic Economics) - Jaudat Iqbal Harris; Aqif Khilmia (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The state has the authority to establish policies that support and protect economic growth and activities. The government, as the executor of collective tasks, is considered entrusted by God to create welfare, justice, and a good life for all people. In this study, the author uses a literature review method to examine the roles, functions, and policies in the economy from an Islamic perspective. The results of this study show that the government plays a crucial role in a country's economy. For example, when Indonesia faced the Covid-19 pandemic, the government took comprehensive actions in the fiscal and monetary sectors. In the fiscal sector, the government refocused activities and reallocated budgets, while in the monetary sector, the Ministry of Finance allocated Rp62.3 trillion from the state budget for Covid-19 handling and control, social protection, and incentives for the business sector.